PENGARUH RARE RESOURCES TERHADAP KEUNGGULAN BERSAING DAN KINERJA USAHA - Ika Purwanti; Noermijati Noermijati; Mintarti Rahayu (Universitas Mercu Buana, 2017)
Abstract. This study aims to examine and analyze the effect of rare resources oncompetitive advantage and business performance. This research was conducted onTenun Ikat SMEs Lamongan. The research sample was 35 business units selected usingsaturated sampling method, that is all the members of the population sampled. The unitof analysis in this study is SMEs and put the owners/managers as respondents. Datawere analyzed by Partial Least Square (PLS) with SmartPLS 3.0 software. The resultsshowed that rare resources are related to competitive advantage and businessperformance, that competitive advantage is related to business performance, and thatcompetitive advantage mediates the rare resources – performance relationship. Keywords: rare resources, competitive advantage, business performance